A consensus statement on birth defects surveillance, prevention, and care in Latin America and the Caribbean - Ignacio Zarante; Paula Hurtado-Villa; Salimah R. Walani; Vijaya Kancherla; Jorge López Camelo; Roberto Giugliani; Boris Groisman; Christopher P. Howson; Pablo Durán (Pan American Health Organization, 2019)
Birth defects contribute up to 21% of the mortality in those under 5 years of age in Latin America and the Caribbean (LAC), and that burden has been compounded by the Zika virus epidemic. In 2001, the March of Dimes launched a series of biennial assemblies called the International Conference on Birth Defects and Disabilities in the Developing World (ICBD). The latest ICBD, in 2017, convened in Bogotá, Colombia, and was attended by over 300 professionals, policymakers, and donors. The conference attendees, a majority of whom were from LAC, supported a call to action in the form of a consensus statement. The consensus statement lists key actions for maximizing birth defects surveillance, prevention, and care in LAC: 1) improving surveillance; 2) reducing risks for birth defects; 3) fortifying staple foods; 4) preventing and treating infections associated with birth defects; 5) implementing newborn screening; 6) providing care and services for people with birth defects and disabilities; 7) involving governments, civil society, and international agencies; and 8) advancing research for birth defects. Implementation and scale-up of evidence-based interventions using multisectoral and multidisciplinary collaborative approaches were endorsed. LAC countries can leverage technology and social media to advance and advocate for approaches identified in the consensus statement. The consensus statement can be used as a guide by both governments and nongovernmental agencies to take immediate steps for improving the quality of life of those living with birth defects and associated disabilities in the LAC countries.